Enhancing Opportunities for Decoding and Knowledge Building through Beginning Texts. - Hiebert, Elfrieda H. (Reading Teacher)
Ensuring effective texts for student reading acquisition is a shared goal. This paper addresses the efficacy of decodable and leveled texts, their word features, and outcomes of reorganizing texts by vowel patterns and topics. Sparse evidence supports one text type's superiority in building a strong reading foundation. Further, the decoding demands of decodable and leveled texts diminish after initial instruction. Studies show reorganizing leveled texts according to a decoding curriculum aids reading acquisition. This finding is the basis for illustrating how existing texts can be reorganized to boost reading volume, apply decoding skills, and offer coherent topic exposure.